The Effects of Nanoencapsulated Curcumin-Fe3O4 on Proliferation and hTERT Gene Expression in Lung Cancer Cells - Sadeghzadeh, Hadi; Pilehvar-Soltanahmadi, Younes; Akbarzadeh, Abolfazl; Dariushnejad, Hassan; Sanjarian, Forough; Zarghami, Nosratollah (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Objective: The aim of the study wasto fabricate curcumin-loaded PLGA-PEG-Fe3O4 nanoparticles and comprise the effects of pure curcumin and curcumin-nanomagnetic encapsulated in PLGA-PEG on cell cytotoxicity and hTERT gene expression in A549 lung cancer cell line. Background: Lung cancer is the most common cancer in men and one of the four main cancers that occurs in women. Telomerase is active in more than 85% of various cancerous cells such as lung cancer while its activity is very low in normal cells. Strong evidences of antitumor effects of curcumin; such as the activation of apoptosis, inhibition of angiogenesis and prevention of metastasis, have been confirmed. However, extensive clinical application of this relatively efficacious agent in cancer therapy has been limited because of poor aqueous solubility, and consequently, minimal systemic bioavailability. Nanoparticle-based targeted drug delivery approach has the potential for rendering curcumin specifically at the favorite site using an external magnetic field. It can also improve availability and circumvent the pitfalls of poor solubility. Methods: Curcumin and Fe3O4 were encapsulated inside the PLGA-PEG co-polymer. Then, the curcumin loaded PLGA-PEG-Fe3O4 nanoparticles were characterized using SEM, FTIR and VSM. In the next step, the cytotoxic effect of different concentrations (0-120 µM) of free curcumin and equivalent doses of curcumin-loaded PLGA-PEG-Fe3O4 was assessed using MTT assay at 24-72 hours. Also, gene expression levels of hTERT were measured through Realtime PCR. Results: By encapsulation of curcumin-Fe3O4, cytotoxicity of the drug substantially increased for all concentrations. IC50 of pure curcumin and nano-encapsulated curcumin during 24, 48 and 72 hours was obtained as 50.5, 49.1 and 48.3 µM and 23.7, 13.6 and 7.3 µM, respectively. Moreover, nano-encapsulated curcumin showed time-dependent cytotoxic effect on A549 cell line during 24, 48, 72 hours in comparison to pure curcumin. In addition, the expression level of the hTERT was reduced with increasing concentrations in both pure and nano-encapsulated curcumin. Compared to pure form, nano-encapsulated curcumin caused further decline in the expression levels of the gene. Conclusion: Curcumin incorporating with Fe3O4 loaded into PLGA-PEG co-polymer, as an effective targeted carrier, can make a promising horizon in targeted lung cancer therapy.
Keywords: Curcumin